1993
DOI: 10.2307/3431524
|View full text |Cite
|
Sign up to set email alerts
|

Lead Toxicity: Current Concerns

Abstract: Over the 20-year period since the first issue of Environmental Health Perspectives was published, there has been considerable progress in the understanding of the potential toxicity of exposure to lead. Many of these advances have been reviewed in published symposia, conferences, and review papers in EHP. This brief review identifies major advances as well as a number of current concerns that present opportunities for prevention and intervention strategies. The major scientific advance has been the demonstrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
166
0
6

Year Published

1996
1996
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(173 citation statements)
references
References 23 publications
1
166
0
6
Order By: Relevance
“…36 Chronic nephropathy from lead exposure often shows interstitial fibrosis and cystic hyperplasia in humans and animals. 2,9,37,38 Lead is also a renal carcinogen in animals 14,39 and possibly in humans. 1 The profound nephrotoxicity induced by lead is characterized by cellular inclusion bodies and renal tubular dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…36 Chronic nephropathy from lead exposure often shows interstitial fibrosis and cystic hyperplasia in humans and animals. 2,9,37,38 Lead is also a renal carcinogen in animals 14,39 and possibly in humans. 1 The profound nephrotoxicity induced by lead is characterized by cellular inclusion bodies and renal tubular dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies on rats and other rodents indicated that blood lead concentrations > 30-40 µg/dL were associated with impairment of spermatogenesis and reduced concentrations of androgens (Pandya et al, 2012;Anjum et al, 2015). However, other animal studies, mainly about histopathological, spermatozoal, and hormonal end points, indicated that certain species and strains were quite resistant to the reproductive toxicity of lead (Goyer, 1993). The human studies focused mainly on semen quality, endocrine function, and birth rates in occupationally exposed subjects, and showed that exposure to concentrations of inorganic lead > 40 µg/dL in blood impaired male reproductive function by reducing sperm count, volume, and density, or changing sperm motility and morfology (Pant et al, 2014;Telišman et al, 2007).…”
Section: Reproductive and Developmental Toxicitymentioning
confidence: 99%
“…Joel Navarrete-Espinosa, M.C., M.A.H., (1) Luz Helena Sanín-Aguirre, M.C., M.S.P., Dr. en C., (2,3) Celia Escandón-Romero, M.S.P., (1) Guadalupe Benitez-Martínez, M.S.P., (1) Gustavo Olaiz-Fernández, M.C., (4) Mauricio Hernández-Avila, M.C., Ph.D. (3) (1) Subjefatura de Epidemiología, Jefatura …”
Section: Niveles De Plomo Sanguíneo En Madres Y Recién Nacidos Derechunclassified
“…E n México, como en muchos otros países de Améri-ca, la exposición ambiental a plomo con el riesgo de efectos deletéreos sobre los sistemas hematopoyético, hepático, renal, reproductivo y gastrointestinal [1][2][3] permanece como una amenaza. Además, en la actualidad, se reconoce su relación con daños neurológicos en niños, expresados a través de retardo en su desarrollo psicomotor.…”
unclassified
See 1 more Smart Citation